Effects of Cu(II) on the Adsorption Behaviors of Cr(III) and Cr(VI) onto Kaolin. - Juanjuan Liu; Wu, Xiaolong; Yandi Hu; Chong Dai; Peng, Qin; Dongli* Liang (Journal of Chemistry, 2016)
The adsorption of Cr(III) or Cr(VI) in the absence and presence of Cu(II) onto kaolin was investigated under pH 2.0–7.0. Results indicated that the adsorption rate was not necessarily proportional to the adsorption capacity. The solutions’ pH values played a key role in kaolin zeta potential , especially the hydrolysis behavior and saturation index of heavy metal ions. In the presence of Cu(II), reached the maximum adsorption capacity of 0.73 mg·g−1 at pH 6.0, while the maximum adsorption capacity for the mixed Cr(VI) and Cu(II) system () was observed at pH 2.0 (0.38 mg·g−1). Comparing the adsorption behaviors and mechanisms, we found that kaolin prefers to adsorb hydrolyzed products of Cr(III) instead of Cr3+ ion, while adsorption sites of kaolin surface were occupied primarily by Cu(II) through surface complexation, leading to Cu(II) inhibited Cr(VI) adsorption. Moreover, Cr(III) and Cr(VI) removal efficiency had a positive correlation with distribution coefficient . Cr(III) and Cr(VI) removal efficiency had a positive correlation with distribution coefficient and that of adsorption affinities of Cr(III) or Cr(VI) on kaolin was found to be Cr(III) < Cr(III)-Cu(II) and Cr(VI) > Cr(VI)-Cu(II).